Assessing the influence of University Brand Image, environment and inter-personal interaction on students university choice: a case of Taraba State University. - Happy L. Michael (African Journal of Behavioural and Scale Development Research, 2020)
This study was undertaken to determine the influence of brand Image, environment and interpersonal interaction on undergraduate students' enrollment into Taraba State University, Jalingo. The study was guided by four research objectives with their corresponding research questions. The research design used to carry out the study was case study design. The population of the study is three thousand eight hundred (3800) first year undergraduate students out of which three hundred and twenty-three (322) were randomly selected from different departments. A questionnaire tagged Student University Choice Criteria Questionnaire (SUCC) was developed and used for data collection. The reliability co-efficient of0.98 was obtained using ordinal Alpha statistics. Data were analyzed using descriptive statistical tools like frequency count and percentages a s well as mean and standard deviation. Findings revealed that tuition fees (3.39), reputation of university (3.35), recognition of certificate (3.35), academic quality (3.29), and geographical location of university (3.29) has the highest influence on students' university choice in the order of magnitude of mean. Findings also showed that female students give more consideration to the university environment when malång the choice of university they wish to enroll in than male students. It was recommended that Taraba State University administrators should make the institution more attractive by Imparting the environment and learning conditions of the university.